If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 12 = 17 + -4x Reorder the terms: 12 + x = 17 + -4x Solving 12 + x = 17 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 12 + x + 4x = 17 + -4x + 4x Combine like terms: x + 4x = 5x 12 + 5x = 17 + -4x + 4x Combine like terms: -4x + 4x = 0 12 + 5x = 17 + 0 12 + 5x = 17 Add '-12' to each side of the equation. 12 + -12 + 5x = 17 + -12 Combine like terms: 12 + -12 = 0 0 + 5x = 17 + -12 5x = 17 + -12 Combine like terms: 17 + -12 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| 160+0.25n=342.50 | | 6(3x-2)=3x+5x | | 10x-25=625 | | x/10-5/2+x=3x/5 | | 3n+1=5n+8 | | 4(m+3)=44 | | 2x+4259=210355 | | 2(x-8)=10 | | 9x+6y=18 | | -2y=4-6x | | 2(3x-1)=4x+5 | | 5(x+5)=64 | | 3(2f-6)+6=36 | | 3n+2(4n-5)-7+n= | | -6x+2x=3x | | x=6x^7+35x^6-169x^5-612x^4+1823x^3+1215x^2-2758x-980 | | 7x+31=91 | | 2x+3=3+2 | | b+3b=56 | | -(1+4x)=3-(3x-3) | | 7y-2=-8-32 | | 2x+8y=12 | | 879+56.23+1.92= | | 2(6)=5x+2 | | -5(t-3)+8t=7t-3 | | (2x+k)(x-2k)=2x^2+9x-18 | | .5x-1.7=.3x-1 | | 10X-30=360 | | f(-3)=x^3+5 | | 5e-2(4-3e)-2e=10 | | -4.3-2*13.2= | | .5x-1.7=.3-1 |